2004
DOI: 10.1111/j.1440-0979.2004.0332.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of a preceptorship course on mental health nursing practice

Abstract: The crisis in the recruitment of nursing graduates into the mental health nursing field dictates the need for assertive and innovative strategies to promote the positive aspects of this field of nursing. A positive clinical experience has been identified as one of the most important determinants of nursing students' attitudes towards mental health nursing. The Centre for Psychiatric Nursing Research and Practice implemented the course "Preceptorship in Psychiatric Nursing" as a means to increase the skill leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…A study completed by Altmiller demonstrated that the application of QSEN core competency skills in the preceptorship enhanced the orthopedic specialty by deepening the focus on patient safety and high-quality care (Altmiller, 2013), ultimately improving patient care outcomes (Hayes, 2001). Furthermore, the positive experience was identified as the most important determinants of nursing students' attitudes toward nursing (Charleston &Happell, 2004) that led to improved patient care outcomes and student competency.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A study completed by Altmiller demonstrated that the application of QSEN core competency skills in the preceptorship enhanced the orthopedic specialty by deepening the focus on patient safety and high-quality care (Altmiller, 2013), ultimately improving patient care outcomes (Hayes, 2001). Furthermore, the positive experience was identified as the most important determinants of nursing students' attitudes toward nursing (Charleston &Happell, 2004) that led to improved patient care outcomes and student competency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study completed by Altmiller demonstrated that the application of QSEN core competency skills in the preceptorship enhanced the orthopedic specialty by deepening the focus on patient safety and high-quality care (Altmiller, 2013), ultimately improving patient care outcomes (Hayes, 2001). Furthermore, the positive experience was identified as the most important determinants of nursing students' attitudes toward nursing (Charleston &Happell, 2004) that led to improved patient care outcomes and student competency. Kim et al 189 Pauly-O'Neill and colleagues (2013) compared Quality and Safety Education for Nurses (QSEN) related student experiences during pediatric clinical and simulation rotations; and reported that three of the six QSEN competencies were observed more often than the others during both the simulation and clinical experiences (Pauly-O'Neill, Prion, Nguyen, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Participants in this study described how within the traditional model, the relatively large ratio of student teacher contributed to less focus on them as individuals and resulted in insufficient time to learn and demonstrate a variety of clinical skills, a finding that also concurred with Bashford [11] and Charleston and Happell. [6] Likewise, interpersonal relationships were regarded by Cambodian students to be the most effective clinical teaching characteristic for a preceptor including her availability to guide them, provide continuous evaluation and exuding self-confidence, good teaching skills and nursing competence. [37] In this study the relationship with the preceptors and the entire working team was greatly enhanced when students worked on shifts and interacted with all members of the clinical team.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Duchsher [4] explained that, practicum experiences are directed toward moving the students to a new level of maturation to ensure that they become professionals who are qualified to undertake the responsibilities that accompany licensure. Preceptorship models are used in Canada, United States, [5] Australia, [6] cns.sciedupress.com…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] While it is strongly agreed that RACFs are appropriate sites for student nurse placement, 10,11 with potential to provide useful learning opportunities, 10,[12][13][14] there has been little critical assessment of the impact on students of staffing and organisational problems associated with aged care practice. Similarly, while it is known that the capacity of aged care providers to support learners has a significant impact on students' placement experience, 8 there has been limited investigation into barriers inhibiting RACFs from providing quality clinical placements.…”
mentioning
confidence: 99%